2017
DOI: 10.1523/jneurosci.3029-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dentate Gyrus Contributes to Retrieval as well as Encoding: Evidence from Context Fear Conditioning, Recall, and Extinction

Abstract: Dentate gyrus (DG) is widely thought to provide a teaching signal that enables hippocampal encoding of memories, but its role during retrieval is poorly understood. Some data and models suggest that DG plays no role in retrieval; others encourage the opposite conclusion. To resolve this controversy, we evaluated the effects of optogenetic inhibition of dorsal DG during context fear conditioning, recall, generalization, and extinction in male mice. We found that (1) inhibition during training impaired context f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
104
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 64 publications
17
104
2
Order By: Relevance
“…Although cannula placements in these studies included the DG, they also contained adjacent areas, not targeting the DG. However, these data appear to contradict at least one recent study demonstrating a role for DG in the retrieval of contextual fear extinction (Bernier et al, 2017). It is speculated that this discrepancy is due to the DG contributes to contextual fear extinction retrieval or auditory fear extinction retrieval through a different mechanism.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Although cannula placements in these studies included the DG, they also contained adjacent areas, not targeting the DG. However, these data appear to contradict at least one recent study demonstrating a role for DG in the retrieval of contextual fear extinction (Bernier et al, 2017). It is speculated that this discrepancy is due to the DG contributes to contextual fear extinction retrieval or auditory fear extinction retrieval through a different mechanism.…”
Section: Discussioncontrasting
confidence: 72%
“…In our study, inactivation of the DG resulted in the disruption of fear renewal, and the rats exhibited extinction memory. Previous studies revealed that extinction is a process that requires both the retrieval of hippocampally stored information and the acquisition of new learning that may be hippocampal-dependent, at least in part (Bernier et al, 2017). The animals may require two memories for extinction retrieval: a fear conditioning memory and an extinction memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DG plays an important role in the discrimination of a similar context from a fearful one (Wu & Hen, ). Inhibition of dorsal DG increases the generalization of fear to an unfamiliar context that was similar to a feared context and impairs fear expression in the conditioned context when it was similar to a neutral context (Bernier et al., ). However, all subregions of the hippocampus are highly interconnected.…”
Section: Discussionmentioning
confidence: 99%